Pengaruh Word of Mouth dan Digital Marketing (Media Sosial Instagram) Terhadap Minat Beli Ulang di RE Caffe Platinum Pekanbaru - Evi betharia; Lie Othman (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to determine the influence of Word of Mouth and Digital Marketing (Social Media Instagram) on Repurchase Intention at Re Caffe Platinum Pekanbaru. In this research, the method used is quantitative descriptive using the SPSS version 25 program. The population in this research is visitors to Re Caffe Platinum Pekanbaru in 2021. The sampling technique used was non-probability with a purposive sampling technique totaling 100 people. The research results show that Word of Mouth has a positive and significant effect on Repurchase Intention, Digital Marketing (Instagram Social Media) has not have a significant effect on Repurchase Intention. The results of research on the influence of Word of Mouth and Digital Marketing (Social Media Instagram) at Re Caffe Platinum Pekanbaru have a significant effect on Repurchase Intention.